Environmental Pollution & the Political Economy of Public Debt - Maximilian Kellner (ZBW - Leibniz Information Centre for Economics, 2020)
This paper analyzes the political economy of government debt when elected politicians decide about the distribution of public funds between a clean and a polluting public good. When provision of the polluting good creates a stock of climate externalities, strategic incentives for the incumbent government arise from both a budget and emission interaction. In this framework, reelection uncertainty leads to inefficiently low public savings (or even debt) which are attenuated by the emission interaction, while first period pollution decreases regardless of the future government's identity. If the incumbent government competes for office against an environmentalists' party, the total welfare loss from emissions also decreases as a direct result of reelection uncertainty.
Keywords: H23; H41; H63; Q54; Q58; 330; emission externality; public debt; political economy